Medication errors in a public hospital in Brazil. - Volpe, Cris Renata Grou; Pinho, Diana Lú';ia Moura; Stival, Marina Morato; de Oliveira Karnikowski, Margo Gomes (British Journal of Nursing, 2014)
This article describes the analysis o f the frequency, type and risk factors relating to errors in the preparation and administration o f medications in patients admitted to a public hospital in Brasilia Federal District, Brazil, which serves a population of approximately 500000 inhabitants. Patients are commonly affected and harmed by medication errors, almost half o f which are preventable. This is a cross-sectional, descriptive and exploratory study conducted in a clinical medicine unit. Direct observations were made by eight nurse technicians. The type o f error, the type of drug involved and associated risk factors were analysed. Relationships between the occurrence of errors and risk factors were studied with logistic regression models. Of the 484 observed doses, 69.5% errors occurred during drug administration, 69.6% during the preparation stage, 48.6% were timing errors, 1.7% were dose-related errors and 9.5% were errors o f omission. More than one error was detected in 34.5% o f occasions. Unlabelled drugs increased the risk o f timing errors by a factor o f 13.72. Interruptions in preparation increased the risk o f errors by a factor of 3.75. Caring for a larger number o f patients (8-9) increased the risk of timing errors by a factor o f 8.27. The research shows the need to manage the risk of medication errors in their real-life contexts by interposing safety barriers between the hazards and potential errors.